Slowmation Integration in Teaching Earth Science: Effects on Grade 11 Students’ Performance and Interest - Pacatua, Rania Banocag; Abdulrachman, Nafisah Moalam (Education, Science, and Technology International Conference, 2025)
This study aimed to investigate the impact of using the student-constructed slowmation video in learning process its effect on performance and interest in Earth Science. This study utilized mixed-method research design to collect data from eighteen (18) Grade 11 students of Adiong Memorial State College (AMSC). The findings showed a notable improvement in the experimental group’s earth science performance (mean score from 17.5 to 40.2), compared to the control group (mean score increased from 16.5 to 28.1). There is no significant difference between the control and experimental group’s performance before intervention. However, there is a significant difference between the control and experimental groups after intervention. The level of interest showed significant improvement after intervention. However, there is significant difference in control and experimental groups after intervention. Overall, this method was seen as innovative tool that improved both the learning experience and students’ interest in earth science. This method increased the earth science performance and interest of the grade 11 students. It is recommended for educators and curriculum makers to consider these results when designing a lesson or curriculum.